2018
DOI: 10.1172/jci.insight.99292
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate dehydrogenase complex stimulation promotes immunometabolic homeostasis and sepsis survival

Abstract: Limited understanding of the mechanisms responsible for life-threatening organ and immune failure hampers scientists' ability to design sepsis treatments. Pyruvate dehydrogenase kinase 1 (PDK1) is persistently expressed in immune-tolerant monocytes of septic mice and humans and deactivates mitochondrial pyruvate dehydrogenase complex (PDC), the gate-keeping enzyme for glucose oxidation. Here, we show that targeting PDK with its prototypic inhibitor dichloroacetate (DCA) reactivates PDC; increases mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
76
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 52 publications
(67 reference statements)
8
76
0
Order By: Relevance
“…THP‐1 cells were maintained in RPMI‐1640 media supplemented with 10% FBS (Gemini Bioproducts, West Sacramento, CA, USA), 2 mM glutamine, and penicillin/streptomycin at a density of between 0.3 × 10 6 and 1 × 10 6 cells per ml; and media replenished every 2–3 d. On the day of the experiments, THP‐1 cells were stimulated with a high dose (1 µg/ml) of LPS ( E. Coli 0111; B4, Sigma‐Aldrich, St. Louis, MO, USA) for 0–24 h, as indicated in the figure legends, in culture media and 5 mM DCA (Sigma‐Aldrich) was added to the cells 30 min before LPS activation; medium was the vehicle control. As previously reported, DCA decreased PDC phosphorylation within 30–60 min (data not shown).…”
Section: Methodssupporting
confidence: 90%
See 4 more Smart Citations
“…THP‐1 cells were maintained in RPMI‐1640 media supplemented with 10% FBS (Gemini Bioproducts, West Sacramento, CA, USA), 2 mM glutamine, and penicillin/streptomycin at a density of between 0.3 × 10 6 and 1 × 10 6 cells per ml; and media replenished every 2–3 d. On the day of the experiments, THP‐1 cells were stimulated with a high dose (1 µg/ml) of LPS ( E. Coli 0111; B4, Sigma‐Aldrich, St. Louis, MO, USA) for 0–24 h, as indicated in the figure legends, in culture media and 5 mM DCA (Sigma‐Aldrich) was added to the cells 30 min before LPS activation; medium was the vehicle control. As previously reported, DCA decreased PDC phosphorylation within 30–60 min (data not shown).…”
Section: Methodssupporting
confidence: 90%
“…We found that PDC activation and pyruvate decarboxylation induced by DCA increased the levels of TCA cycle intermediates that usually control anabolism, decreased the level of itaconate that supports tolerance, and enhanced catabolism‐dependent anaplerotic functions of BCAAs. Our findings support the concept that PDC is a crucial mitochondrial energy homeostat and that PDK is a druggable target for treating clinical inflammatory shock syndromes …”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations